A Comparative Study of Fairy Tale and Rap Narratives: Spaces Specificity - Kravchenko Nataliia Кymivna; Davydova, Tetiana Vasylivna; Goltsova, Marianna Gennadiivna (Journal of History Culture and Art Research, 2020)
The paper identifies the similarities and differences between fairy tale and rap narratives from the viewpoint of their specificity in space. Three spaces with their structuring topoi and loci have been investigated in their metaphorical, narrative, and symbolic manifestations. First: the spatial organization of rap and fairy tale narratives may include several possible worlds: the world of the Hero’s past before his journey through life and fairy tale transformation; the world of the Hero’s present after his transformation, marked by new loci consistent with his new status of the Hero, as well as the intangible symbolic world, the contact with which is a prerequisite for the revival of the fairy tale hero and optional – for the lyrical hero of rap narrative. Second: the world of the Hero’s past based on ambivalent ’ghetto’ topos whose conceptual space is constructed by conceptual metaphors life is a broken boogie, ghetto is belly of a monster, living in ghetto is fighting on the line of fire. Ghetto topos correlates with the topos of the forest as the place of the tale Hero trials, rooted in the archetypal motive of initiation. Third: the locus of "home/house" is conceptualized in rap lyrics and a fairy tale as a familiar, closed and safe space, contrasted, respectively, with topoi of ’ghetto’ and forest with their manifesting loci on criteria "open/closed", "unexplored/familiar", "mastered/unpredictable", "dangerous – safe". Fourth: loci in alternative worlds may acquire anthropomorphic properties, changing along the axis of "living/non-living" and "passive/active". Both in fairy tale and rap narratives, the symbolic "world" may involve the topoi of the road, sky, and forest based on archetypes, related to a spiritual search of the Hero.